2017
DOI: 10.1111/rode.12346
|View full text |Cite
|
Sign up to set email alerts
|

Waste not, want not: The efficiency of health expenditure in emerging and developing economies

Abstract: Public health spending is low in emerging and developing economies relative to advanced economies and health outputs and outcomes need to be substantially improved. Simply increasing public expenditure in the health sector, however, may not significantly affect health outcomes if the efficiency of this spending is low. This paper quantifies the inefficiency of public health expenditure and the associated potential gains for emerging and developing economies using a stochastic frontier model that controls for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 24 publications
1
79
2
2
Order By: Relevance
“…169 Africa reports higher per capita health spending and worse health outcomes than South Asia, the most comparable region in terms of health expenditure. 170 This categorisation again masks important between-country imbalances: Namibia and Togo are among the most efficient spenders, while Lesotho, Mali, and Sierra Leone lie at the other extreme.…”
Section: Improving Health Spending Efficiencymentioning
confidence: 99%
“…169 Africa reports higher per capita health spending and worse health outcomes than South Asia, the most comparable region in terms of health expenditure. 170 This categorisation again masks important between-country imbalances: Namibia and Togo are among the most efficient spenders, while Lesotho, Mali, and Sierra Leone lie at the other extreme.…”
Section: Improving Health Spending Efficiencymentioning
confidence: 99%
“…The measurement methods are normally parameter method as stochastic frontier analysis (SFA), and non-parameter method as data envelopment analysis (DEA). Grigoli and Kapsoli adopted SFA to study medical and health output efficiency in emerging countries and development countries, and concluded that the medical and health output efficiency was the lowest in African entities [10]. Berta et al applied traditional DEA method to measure operation efficiency of hospitals in Italy, and found that the technology efficiency of private hospitals was lower than not-profit public hospitals [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the international level, comparative studies abound, but with dissimilar results. Most of them show good results for Peru in terms of expenditure and life expectancy, healthy years, or other indicators (31,32). In a comparison of five rankings for 191 countries, Peru is situated between the first and second efficiency tercile (33).…”
Section: Efficiency Of Public Expenditurementioning
confidence: 99%